PENGARUH STORE LAYOUT DAN ATMOSPHERE TERHADAP SHOPPING INTENTION ZALORA ONLINE STORE - Sany Surya (Perpustakaan Universitas Surabaya, 2015)
This study aims to know and analyze the influence of layout design and atmosphere on purchase intention trough emotional arousal and attitude toward the website. This research using SPSS 1.6 and Lisrel 8.7 software. Data collected directly from respondents who meet the specified characteristics of the population by distributing questionnaires. The samples used in this study was 150 respondents. The results of this study showed the influence of layout design on emotional arousal and attitude toward the website, the influence of atmosphere on emotional arousal, the influence of emotional arousal on attitude toward the website, the influence of emotional arousal on purchase intention, the influence of attitude toward the website on purchase intention, while the influence of atmosphere on emotional arousal, and the influence of emotional arousal on purchase intention of Zalora online store are rejected.